Impaired T helper cell responses in human immunodeficiency virus‐exposed uninfected newborns - Yesenia Brito‐Pérez; Rodrigo T. Camacho‐Pacheco; Noemi Plazola‐Camacho; Diana Soriano‐Becerril; Irma A. Coronado‐Zarco; Gabriela Arreola‐Ramírez; Gabriela González‐Pérez; Alma Herrera‐Salazar; Julio Flores‐González; Mextli Y. Bermejo‐Haro; Brenda G. Casorla‐Cervantes; Ismael A. Soto‐López; et al. (Immunity, Inflammation and Disease)
Abstract Introduction HIV‐exposed uninfected (HEU) newborns suffer from higher risks of opportunistic infections during the first months of life compared to HIV‐unexposed uninfected (HUU) newborns. Alterations in thymic mass, amounts of T helper (Th) cells, T‐cell receptor diversity, and activation markers have been found in HEU newborns, suggesting alterations in T cell ontogeny and differentiation. However, little is known about the ability of these cells to produce specialized Th responses from CD4+ T cells. Method To characterize the Th cell profile, we evaluated the frequency of Th1 (CD183+CD194−CD196−/CXCR3+CCR4−CCR6−), Th2 (CD183−CD194+CD196−/CXCR3−CCR4+CCR6−), Th17 (CD183−CD194+CD196+/CXCR3−CCR4+CCR6+), and CD4+CD25++ blood T‐cell phenotypes in 50 HEU and 25 HUU newborns. Early activation markers on CD4+ T cells and the Th cytokine profile produced from mononuclear cells under polyclonal T cell stimulation were also studied. Additionally, we probed the ability of CD4+ T cells to differentiate into interferon (IFN)‐γ‐producing Th1 CD4+ T cells in vitro. Results Lower percentages of differentiated Th1, Th2, Th17, and CD4+CD25++ T cells were found in blood from HEU newborns than in blood from HUU newborns. However, polyclonally stimulated Th cells showed a similar ability to express CD69 and CD279 but produced less secreted interleukin (IL)‐2 and IL‐4. Interestingly, under Th1 differentiation conditions, the percentages of CD4+IFN‐γ+ T cells and soluble IFN‐γ were higher in HEU newborns than in HUU newborns. Conclusion HEU neonates are born with reduced proportions of differentiated Th1/Th2/Th17 and CD4+CD25++ T cells, but the intrinsic abilities of CD4+ T cells to acquire a Th1 profile are not affected by the adverse maternal milieu during development.